Taking away David's sling*: environmental justice and land-use conflict in extractive resource development. Issue 8 (3rd August 2017) - Kennedy, Amanda; Schafft, Kai A.; Howard, Tanya M.
ABSTRACT: Exploring cases of gas and coal extraction in Australia and the U.S.A., this paper considers instances in which legal and political frameworks have been used to prioritise development interests and minimise opportunities for community objection. Two case studies illustrate the role of law and the influence of politics on environmental conflict, conflict resolution, and participation in decision-making associated with resource extraction. A range of barriers to meaningful community participation in land-use decision-making are exposed by combining legal and non-legal concepts of equity and justice with ideologies of democracy and representation. These include asymmetry in information and resources available to parties; instances of misrecognition of weaker participants; and examples of malrecognition, where community attempts to engage democratic rights of public participation were thwarted by the strategic and deliberate actions of both industry and government. This paper illustrates the limits of current legal approaches to addressing land-use conflict and contributes to the developing scholarship of environmental justice as an analytic framework for addressing complex environmental and social justice issues.